The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1002/1097-0142(19891115)64:10<2154::aid-cncr2820641030>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell fibroblastoma. A juvenile form of dermatofibrosarcoma protuberans

Abstract: A clinicopathologic analysis of 28 cases of giant cell fibroblastoma (GCF), a rare mesenchymal tumor occurring predominantly in the first decade of life, is presented. This disease presented as a painless, slowly enlarging, subcutaneous mass. The tumor recurred locally in 47% of the patients; however, metastasis was not detected. On microscopic examination, GCF showed an unique combination of spindle cell patterns, pleomorphic and multinucleated giant cells, myxoid areas, and distinctive sinusoid-like spaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(116 citation statements)
references
References 9 publications
3
110
0
3
Order By: Relevance
“…However, we consider this to be highly significant and constant feature, as it was observed in all of our cases and is also visible in some figures in previous reports [16,19]. In some areas the stroma strongly resembled the appearance of giant cell fibroblastoma (GCF), where a pseudoangiomatous pattern is a feature [12,23]. Another lesion featuring spaces reminiscent of vascular lumina is pseudoangiomatous stromal hyperplasia of the mammary gland (PASH) [2,20,26].…”
Section: Discussionsupporting
confidence: 80%
“…However, we consider this to be highly significant and constant feature, as it was observed in all of our cases and is also visible in some figures in previous reports [16,19]. In some areas the stroma strongly resembled the appearance of giant cell fibroblastoma (GCF), where a pseudoangiomatous pattern is a feature [12,23]. Another lesion featuring spaces reminiscent of vascular lumina is pseudoangiomatous stromal hyperplasia of the mammary gland (PASH) [2,20,26].…”
Section: Discussionsupporting
confidence: 80%
“…We independently and a priori observed that several tumors had angiectatic spaces lined by floret-type giant cells and stromal collagen, identical to those observed in a known soft tissue tumor, GCF. GCF is primarily a truncal tumor of childhood, the myxoid, benign variant of adult dermatofibrosarcoma protuberans (DFSP) [39,40]. Although there has been a case associating DFSP with GCA in the skin [41], we suspect rather that this case was probably a combination of GCF and DFSP, a common hybrid occurrence.…”
Section: Discussionmentioning
confidence: 98%
“…However, a spectrum of histologic variants [6,[21][22][23][24] and rare diagnostically indeterminate lesions [25] have been described. In such cases, documentation of the highly specific genetic rearrangements is desirable.…”
Section: Discussionmentioning
confidence: 99%